Amazonocrinis nigriterrae gen. Nov., sp. nov., atlanticothrix silvestris gen. nov., sp. nov. and dendronalium phyllosphericum gen. nov., sp. nov., nostocacean cyanobacteria from brazilian environments - Alvarenga, Danillo Oliveira; Andreote, Ana Paula Dini; Branco, Luis Henrique Zanini [UNESP]; Delbaje, Endrews; Cruz, Renata Beatriz; Varani, Alessandro de Mello [UNESP]; Fiore, Marli Fátima (Microbiology Society, 2021)
The cyanobacterial genus Nostoc is an important contributor to carbon and nitrogen bioavailability in terrestrial ecosystems and a frequent partner in symbiotic relationships with non-diazotrophic organisms. However, since this currently is a polyphy-letic genus, the diversity of Nostoc-like cyanobacteria is considerably underestimated at this moment. While reviewing the phylogenetic placement of previously isolated Nostoc-like cyanobacteria originating from Brazilian Amazon, Caatinga and Atlantic forest samples, we detected 17 strains isolated from soil, freshwater, rock and tree surfaces presenting patterns that diverged significantly from related strains when ecological, morphological, molecular and genomic traits were also considered. These observations led to the identification of the evaluated strains as representative of three novel nostocacean genera and species: Amazonocrinis nigriterrae gen. nov., sp. nov.; Atlanticothrix silvestris gen. nov., sp. nov.; and Dendronalium phyllosphericum gen. nov., sp. nov., which are herein described according to the rules of the International Code of Nomenclature for algae, fungi and plants. This finding highlights the great importance of tropical and equatorial South American ecosystems for harbouring an unknown microbial diversity in the face of the anthropogenic threats with which they increasingly struggle.
Keywords: Anthropogenic dark earth; Nitrogen fixation; Nostocaceae; Phyllosphere; Phylogenomics